Penerapan Metode VIKOR Dalam Pemilihan Calon Peserta Olimpiade Olahraga Siswa Nasional (O2SN) - Muhammad W P Agatmadja; Atika Suri; Agustin Agustin (JURIKOM (Jurnal Riset Komputer), 2018)
National Student Sports Olympiad is a national event to find new seeds of Indonesia in the field of sports. Students who follow the National Student Sports Olympiad are students who pass the selection held at the district/city and province that have been determined. The National Student Sports Olympiad is based because of the number of students' interest in sports. the holding of this activity aims to improve physical health, and student creativity. Until now, many students have participated in this competition, but in the selection of new applicants for too long because they still use the manual system. In this study, researchers used the VIKOR method for the selection of candidates for Olympic National Students Sports Competition which is expected to facilitate the way it works